A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

An In Vitro Approach for Investigating the Safety of Lipotransfer after Breast-Conserving Therapy - Promny, Theresa; Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kadam, Sheetal; Schmid, Rafael; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2022)
The application of lipotransfer after breast-conserving therapy (BCT) and irradiation in breast cancer patients is an already widespread procedure for reconstructing volume deficits of the diseased breast. Nevertheless, the safety of lipotransfer has still not been clarified yet due to contradictory data. The goal of this in vitro study was to further elucidate the potential effects of lipotransfer on the irradiated remaining breast tissue. The mammary epithelial cell line MCF-10A was co-cultured with the fibroblast cell line MRC-5 and irradiated with 2 and 5 Gy. Afterwards, cells were treated with conditioned medium (CM) from adipose-derived stem cells (ADSC), and the effects on the cellular functions of MCF-10A cells and on gene expression at the mRNA level in MCF-10A and MRC-5 cells were analyzed. Treatment with ADSC CM stimulated transmigration and invasion and decreased the surviving fraction of MCF-10A cells. Further, the expression of cytokines, extracellular, and mesenchymal markers was enhanced in mamary epithelial cells. Only an effect of ADSC CM on irradiated fibroblasts could be observed. The present data suggest epithelial–mesenchymal transition-like changes in the epithelial mammary breast cell line. Thus, the benefits of lipotransfer after BCT should be critically weighed against its possible risks for the affected patients.<br

Auswirkungen der Kombination des Ligase IV Inhibitors SCR7 mit ionisierender Strahlung auf HNO-Tumorzelllinien und Normalgewebszellen - Hildebrand, Laura; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Comparison of different CDK4/6 Kinase Inhibitors (Palbociclib, Ribociclib, Abemaciclib) and their Influence on the Effectiveness of simultaneous Radiation Therapy - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

DNA as the main target in radiotherapy—a historical overview from first isolation to anti-tumour immune response - Frey, Benjamin; Borgmann, Kerstin; Jost, Tina; Greve, Burkhard; Oertel, Michael; Micke, Oliver; Eckert, Franziska (Strahlentherapie und Onkologie, 2023)
DNA damage is one of the foremost mechanisms of irradiation at the biological level. After the first isolation of DNA by Friedrich Miescher in the 19th century, the structure of DNA was described by Watson and Crick. Several Nobel Prizes have been awarded for DNA-related discoveries. This review aims to describe the historical perspective of DNA in radiation biology. Over the decades, DNA damage has been identified and quantified after irradiation. Depending on the type of sensing, different proteins are involved in sensing DNA damage and repairing the damage, if possible. For double-strand breaks, the main repair mechanisms are non-homologous end joining and homologous recombination. Additional mechanisms are the Fanconi anaemia pathway and base excision repair. Different methods have been developed for the detection of DNA double-strand breaks. Several drugs have been developed that interfere with different DNA repair mechanisms, e.g., PARP inhibitors. These drugs have been established in the standard treatment of different tumour entities and are being applied in several clinical trials in combination with radiotherapy. Over the past decades, it has become apparent that DNA damage mechanisms are also directly linked to the immune response in tumours. For example, cytosolic DNA fragments activate the innate immune system via the cGAS STING pathway.
CRIS-Team Scopus Importer:2023-09-01
Keywords: DNA double-strand breaks; DNA repair; History; Immunooncology; Radiobiology

Dual mtor/dna-pk inhibitor cc-115 induces cell death in melanoma cells and has radiosensitizing potential - Bürkel, Felix; Jost, Tina; Hecht, Markus; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
CC-115 is a dual inhibitor of the mechanistic target of rapamycin (mTOR) kinase and the DNA-dependent protein kinase (DNA-PK) that is currently being studied in phase I/II clinical trials. DNA-PK is essential for the repair of DNA-double strand breaks (DSB). Radiotherapy is frequently used in the palliative treatment of metastatic melanoma patients and induces DSBs. Melanoma cell lines and healthy-donor skin fibroblast cell lines were treated with CC-115 and ionizing irradiation (IR). Apoptosis, necrosis, and cell cycle distribution were analyzed. Colony forming assays were conducted to study radiosensitizing effects. Immunofluorescence microscopy was performed to determine the activity of homologous recombination (HR). In most of the malign cell lines, an increasing concentration of CC-115 resulted in increased cell death. Furthermore, strong cytotoxic effects were only observed in malignant cell lines. Regarding clonogenicity, all cell lines displayed decreased survival fractions during combined inhibitor and IR treatment and supra-additive effects of the combination were observable in 5 out of 9 melanoma cell lines. CC-115 showed radiosensitizing potential in 7 out of 9 melanoma cell lines, but not in healthy skin fibroblasts. Based on our data CC-115 treatment could be a promising approach for patients with metastatic melanoma, particularly in the combination with radiotherapy.
CRIS-Team Scopus Importer:2020-12-25
Keywords: DNA repair; DNA-PK; Homologous recombination (HR); Kinase inhibitor; Melanoma; MTOR; Non-homologous end-joining (NHEJ); Radiosensitivity

Effect of the kinase-inhibitor Palbociclib on radio-therapeutic treatment in a 3D cell culture model - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36492

Effects of Combination Therapy of Kinase Inhibitors and ionizing Radiation on ENT Tumor Cell Lines and Normal Tissue Cells - Faulhaber, E. -M; Scheper, J.; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Enhancing the Effect of Combination Therapy with the PARP Inhibitor Talazoparib and ionizing Radiation on Melanoma Cell Lines - Proebstle, Stephanie; Jost, Tina; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36488

Ex vivo radiosensitivity is increased in non-cancer patients taking valproate - Stritzelberger, Jenny; Lainer, Jennifer; Gollwitzer, Stefanie; Graf, Wolfgang; Jost, Tina; Lang, Johannes; Müller, Tamara; Schwab, Stefan; Fietkau, Rainer; Hamer, Hajo; Distel, Luitpold (BMC Neurology, 2020)
Background: Valproate (VPA) is a commonly prescribed antiepileptic drug for patients experiencing epileptic seizures due to brain tumors. VPA increases radiation sensitivity in various tumor cells in vitro due to complex mechanisms. This could make tumors more vulnerable to ionizing radiation or overcome radioresistance. Yet, clinical data on possible improvement of tumor control by adding VPA to tumor therapy is controversial. Potentially radiosensitizing effects of VPA on healthy tissue remain unclear. To determine individual radiosensitivity, we analyzed blood samples of individuals taking VPA. Methods: Ex vivo irradiated blood samples of 31 adult individuals with epilepsy were studied using 3-color fluorescence in situ hybridization. Aberrations in chromosomes 1, 2 and 4 were analyzed. Radiosensitivity was determined by the mean breaks per metaphase (B/M) and compared to age-matched (2:1) healthy donors. Results: The patient cohort (n = 31; female: 38.7%) showed an increase of their average B/M value compared to healthy individuals (n = 61; female: 56.9%; B/M: 0.480 ± 0.09 vs. 0.415 ± 0.07; p =.001). The portion of radiosensitive (B/M > 0.500) and distinctly radiosensitive individuals (B/M > 0.600) was increased in the VPA group (54.9% vs. 11.3 and 9.7% vs. 0.0%; p <.001). In 3/31 patients, radiosensitivity was determined prior to and after VPA treatment and radiosensitivity was increased by VPA-treatment. Conclusions: In our study, we confirmed that patients treated with VPA had an increased radiosensitivity compared to the control group. This could be considered in patients taking VPA prior to the beginning of radiotherapy to avoid toxic side effects of VPA-treatment.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 3-colour fluorescence-in-situ-hybridization; Breaks per metaphase; Individual radiosensitivity; Valproate

Fisetin induces DNA double-strand break and interferes with the repair of radiation-induced damage to radiosensitize triple negative breast cancer cells - Khozooei, Shayan; Lettau, Konstanze; Barletta, Francesca; Jost, Tina; Rebholz, Simone; Veerappan, Soundaram; Franz-Wachtel, Mirita; Macek, Boris; Iliakis, George; Distel, Luitpold; Zips, Daniel; Toulany, Mahmoud (Journal of Experimental & Clinical Cancer Research, 2022)
Background Triple-negative breast cancer (TNBC) is associated with aggressiveness and a poor prognosis. Besides surgery, radiotherapy serves as the major treatment modality for TNBC. However, response to radiotherapy is limited in many patients, most likely because of DNA damage response (DDR) signaling mediated radioresistance. Y-box binding protein-1 (YB-1) is a multifunctional protein that regulates the cancer hallmarks among them resisting to radiotherapy-induced cell death. Fisetin, is a plant flavonol of the flavonoid family of plant polyphenols that has anticancer properties, partially through inhibition of p90 ribosomal S6 kinase (RSK)-mediated YB-1 phosphorylation. The combination of fisetin with radiotherapy has not yet been investigated. Methods Activation status of the RSK signaling pathway in total cell lysate and in the subcellular fractions was analyzed by Western blotting. Standard clonogenic assay was applied to test post-irradiation cell survival. gamma H2AX foci assay and 3 color fluorescence in situ hybridization analyses were performed to study frequency of double-strand breaks (DSB) and chromosomal aberrations, respectively. The underlying repair pathways targeted by fisetin were studied in cells expressing genomically integrated reporter constructs for the DSB repair pathways via quantifying the expression of green fluorescence protein by flow cytometry. Flow cytometric quantification of sub-G1 cells and the protein expression of LC3-II were employed to measure apoptosis and autophagy, respectively. Kinase array and phosphoproteomics were performed to study the effect of fisetin on DDR response signaling. Results We showed that the effect of fisetin on YB-1 phosphorylation in TNBC cells is comparable to the effect of the RSK pharmacological inhibitors. Similar to ionizing radiation (IR), fisetin induces DSB. Additionally, fisetin impairs repair of IR-induced DSB through suppressing the classical non-homologous end-joining and homologous recombination repair pathways, leading to chromosomal aberration as tested by metaphase analysis. Effect of fisetin on DSB repair was partially dependent on YB-1 expression. Phosphoproteomic analysis revealed that fisetin inhibits DDR signaling, which leads to radiosensitization in TNBC cells, as shown in combination with single dose or fractionated doses irradiation. Conclusion Fisetin acts as a DSB-inducing agent and simultaneously inhibits repair of IR-induced DSB. Thus, fisetin may serve as an effective therapeutic strategy to improve TNBC radiotherapy outcome.
CRIS-Team WoS Importer:2022-09-02

Fisetin induces DNA double-strand break and interferes with the repair of radiation-induced damage to radiosensitize triple negative breast cancer cells - Khozooei, Shayan; Lettau, Konstanze; Barletta, Francesca; Jost, Tina; Rebholz, Simone; Veerappan, Soundaram; Franz-Wachtel, Mirita; Macek, Boris; Iliakis, George; Distel, Luitpold; Zips, Daniel; Toulany, Mahmoud (Journal of Experimental & Clinical Cancer Research, 2022)
Background Triple-negative breast cancer (TNBC) is associated with aggressiveness and a poor prognosis. Besides surgery, radiotherapy serves as the major treatment modality for TNBC. However, response to radiotherapy is limited in many patients, most likely because of DNA damage response (DDR) signaling mediated radioresistance. Y-box binding protein-1 (YB-1) is a multifunctional protein that regulates the cancer hallmarks among them resisting to radiotherapy-induced cell death. Fisetin, is a plant flavonol of the flavonoid family of plant polyphenols that has anticancer properties, partially through inhibition of p90 ribosomal S6 kinase (RSK)-mediated YB-1 phosphorylation. The combination of fisetin with radiotherapy has not yet been investigated. Methods Activation status of the RSK signaling pathway in total cell lysate and in the subcellular fractions was analyzed by Western blotting. Standard clonogenic assay was applied to test post-irradiation cell survival. γH2AX foci assay and 3 color fluorescence in situ hybridization analyses were performed to study frequency of double-strand breaks (DSB) and chromosomal aberrations, respectively. The underlying repair pathways targeted by fisetin were studied in cells expressing genomically integrated reporter constructs for the DSB repair pathways via quantifying the expression of green fluorescence protein by flow cytometry. Flow cytometric quantification of sub-G1 cells and the protein expression of LC3-II were employed to measure apoptosis and autophagy, respectively. Kinase array and phosphoproteomics were performed to study the effect of fisetin on DDR response signaling. Results We showed that the effect of fisetin on YB-1 phosphorylation in TNBC cells is comparable to the effect of the RSK pharmacological inhibitors. Similar to ionizing radiation (IR), fisetin induces DSB. Additionally, fisetin impairs repair of IR-induced DSB through suppressing the classical non-homologous end-joining and homologous recombination repair pathways, leading to chromosomal aberration as tested by metaphase analysis. Effect of fisetin on DSB repair was partially dependent on YB-1 expression. Phosphoproteomic analysis revealed that fisetin inhibits DDR signaling, which leads to radiosensitization in TNBC cells, as shown in combination with single dose or fractionated doses irradiation. Conclusion Fisetin acts as a DSB-inducing agent and simultaneously inhibits repair of IR-induced DSB. Thus, fisetin may serve as an effective therapeutic strategy to improve TNBC radiotherapy outcome.<br

Gender parity in radiation oncology in Germany: a 2024 analysis of professional roles and academic training - Besserer, Angela; Jost, Tina; Wittig, Andrea; Schmidt, Livia; Deloch, Lisa; Caglayan, Lara; Flechl, Birgit; Fraller, Astrid; Hörner-Rieber, Juliane; Petersen, Cordula; Trommer, Maike; DEGRO, A. G.FiRO (Strahlentherapie und Onkologie, 2025)
Purpose: Despite some progress, gender inequalities remain prevalent in many medical fields, including radiation oncology (RO). This study investigates gender parity in RO in Germany, with a particular focus on the distribution of professional positions and academic qualifications. Methods: Using data from the German Society of Radiation Oncology (DEGRO), we analyzed gender representation in various roles including resident physicians, specialists, senior physicians, leading positions, and heads of university departments. Additionally, academic achievements such as doctoral degrees and professorships were examined. Temporal trends were assessed by comparing data from 2006, while interdisciplinary comparisons were made using current data from other medical specialties. Results: An increase in the proportion of female members was found, rising by a factor of 1.85 (2006: 570 vs. 2024: 1055). However, significant gender disparities persist, particularly at higher professional levels. Leadership positions remain male dominated, with women holding only 18.9% of full professorships in 2024. In 2006, just 1 in 9 university chair positions and 1 in 40 professorships were occupied by women. These figures had improved by 2024, with women holding 1 in 5 university chair positions and professorships. Conclusion: Despite progress in representation, significant gender disparities remain in leadership and academic positions within RO. Structural barriers continue to impede women’s career advancement. This study identifies these obstacles and advocates for targeted initiatives to foster gender equity, including mentorship programs and family-friendly policies. The ultimate goal is to establish an equitable and appealing professional environment for future generations in RO.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Gender distribution; Leadership diversity; Leaky pipeline; Women; Workforce equity

Induction of Senescence in Head and Neck Tumor Cells by Combination of Irradiation and DNA Repair Inhibitors - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of alectinib and crizotinib on ionizing radiation - in vitro analysis of ALK/ROS1-wildtype lung tissue cells - Jost, Tina; Schultz, Ann Kristin; Frey, Benjamin; Vu, Jennifer; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Neoplasia, 2022)
(1) Background: Just little is known about the interaction of ALK/ROS1-targeting kinase inhibitors with ionizing radiation (IR), particularly regarding side effects. We investigated the toxicity in two different lung cell lines both ALK/ROS1 wildtype (healthy and tumor origin) as representatives for normal lung tissue; (2) Methods: Human lung cell line BEAS-2B and malignant A549 lung cancer cells (ALK/ROS1 wt) were treated with alectinib or crizotinib, 2 Gy irradiation or a combination of KI and IR. Cell toxicity was analyzed by cell death (Annexin, 7AAD), colony forming, migration assay and live-cell imaging (TMRM, DRAQ7, Caspase3/7). Cell cycle (Hoechst) were analyzed by flow cytometry; (3) Results: Crizotinib led to higher cell death rates than alectinib, when cells were treated with 10 µM KI. Alectinib induced a more intense growth inhibition of colonies. Both inhibitors showed additive effects in combination with irradiation. Combination treatment (IR + KI) does not lead to synergistic effect on neither cell death nor colony forming; (4) Conclusions: The influence of simultaneous KI and IR was studied in non-mutated ALK/ROS1 cell lines. Both KIs seems to be well tolerated in combination with thoracic radiotherapy and lacked synergistic reinforcement in cellular toxicity. This supports the feasibility of ALK/ROS1 inhibition in combination with thoracic irradiation in future clinical trials.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Alectinib; Crizotinib; Lung cells; Normal tissue; Radiotherapy; Side effects

Influence of CDK4/6 Inhibitors and Ionizing Radiation on Senescence in Breast Cancer Cells - Quarz, L.; Jost, Tina; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Influence of gender on radiosensitivity during radiochemotherapy of advanced rectal cancer - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Büttner-Herold, Maike; Weber, Klaus; Denz, Axel; Grützmann, Robert; Hartmann, Arndt; Geinitz, Hans; Fietkau, Rainer; et al. (Cancers, 2022)
Gender is increasingly recognized as an important factor in medicine, although it has long been neglected in medical research in many areas. We have studied the influence of gender in advanced rectal cancer with a special focus on radiosensitivity. For this purpose, we studied a cohort of 495 men (84.1% ≥ T3, 63.6% N1, 17.6%, M1) and 215 women (84.2% ≥ T3, 56.7% N1, 22.8%, M1) who all suffered from advanced rectal cancer and were treated with radiochemotherapy. The energy deposited, DNA double-strand break (dsb) repair, occurrence of chromosomal aberrations, duration of therapy, tumor regression and tumor-infiltrating lymphocytes, laboratory parameters, quality of life and survival were assessed. The residual DNA dsb damage 24 h after irradiation in lymphocytes was identical in both sexes. Furthermore, chromosomal aberrations accurately reflecting radiosensitivity, were similar in both sexes. There were no gender-dependent differences in tumor regression, tumor-infiltrating lymphocytes and outcome indicating no differences in the radiosensitivity of cancer cells. The irradiated tumor volume in women was slightly lower than in men, related to body weight, no difference was observed. However, when the total energy deposited was calculated and related to the body weight, women were exposed to higher amounts of ionizing radiation. During radiochemotherapy, decreases in blood lymphocyte counts and albumin and several quality-of-life parameters such as nausea and vomiting, loss of appetite, and diarrhea were significantly worse in women. There is no difference in radiation sensitivity between men and women in both normal tissue and tumors. During radiochemotherapy, the quality of life deteriorates more in women than in men. However, women also recover quickly and there are no long-term differences in quality of life.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Blood values; Deposited energy; DNA double-strand breaks; Gender; Quality of life; Radiochemotherapy; Radiosensitivity; Radiosensitivity; Rectal cancer

Influence of the ALK Kinase Inhibitors Crizotinib and Alectinib on healthy and malignant Lung Cell Lines in a Combination Therapy with ionizing Radiation - Schultz, A. -K; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of the ATR and ATM Kinase Inhibitors VE822 and AZD0156 on Melanoma Cell Lines in Combination Therapy with ionizing Radiation - Scheper, J. S. S.; Jost, Tina; Faulhaber, E. -M; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of the Kinase Inhibitor Palbociclib on the Migration of malignant and non-malignant Cells under Irradiation - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Inhibition of ATM or ATR in combination with hypo-fractionated radiotherapy leads to a different immunophenotype on transcript and protein level in HNSCC - Meidenbauer, Julia; Wachter, Matthias; Schulz, Sebastian; Mostafa, Nada; Zülch, Lilli; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Jost, Tina (Frontiers in Oncology, 2024)
Background: The treatment of head and neck tumors remains a challenge due to their reduced radiosensitivity. Small molecule kinase inhibitors (smKI) that inhibit the DNA damage response, may increase the radiosensitivity of tumor cells. However, little is known about how the immunophenotype of the tumor cells is modulated thereby. Therefore, we investigated whether the combination of ATM or ATR inhibitors with hypo-fractionated radiotherapy (RT) has a different impact on the expression of immune checkpoint markers (extrinsic), the release of cytokines or the transcriptome (intrinsic) of head and neck squamous cell carcinoma (HNSCC) cells. Methods: The toxic and immunogenic effects of the smKI AZD0156 (ATMi) and VE-822 (ATRi) in combination with a hypo-fractionated scheme of 2x5Gy RT on HPV-negative (HSC4, Cal-33) and HPV-positive (UM-SCC-47, UD-SCC-2) HNSCC cell lines were analyzed as follows: cell death (necrosis, apoptosis; detected by AnxV/PI), expression of immunostimulatory (ICOS-L, OX40-L, TNFSFR9, CD70) and immunosuppressive (PD-L1, PD-L2, HVEM) checkpoint marker using flow cytometry; the release of cytokines using multiplex ELISA and the gene expression of Cal-33 on mRNA level 48 h post-RT. Results: Cell death was mainly induced by the combination of RT with both inhibitors, but stronger with ATRi. Further, the immune phenotype of cancer cells, not dying from combination therapy itself, is altered predominantly by RT+ATRi in an immune-stimulatory manner by the up-regulation of ICOS-L. However, the analysis of secreted cytokines after treatment of HNSCC cell lines revealed an ambivalent influence of both inhibitors, as we observed the intensified secretion of IL-6 and IL-8 after RT+ATRi. These findings were confirmed by RNAseq analysis and further the stronger immune-suppressive character of RT+ATMi was enlightened. We detected the down-regulation of a central protein of cytoplasmatic sensing pathways of nucleic acids, RIG-1, and found one immune-suppressive target, EDIL3, strongly up-regulated by RT+ATMi. Conclusion: Independent of a restrictive toxicity, the combination of RT + either ATMi or ATRi leads to comprehensive and immune-modulating alterations in HNSCC. This includes pro-inflammatory signaling induced by RT + ATRi but also anti-inflammatory signals. These findings were confirmed by RNAseq analysis, which further highlighted the immune-suppressive nature of RT + ATMi.
CRIS-Team Scopus Importer:2024-10-25
Keywords: ATM inhibition; ATR inhibition; DNA damage repair; HNSCC; immunomodulation; kinase inhibitors

In the Case of Radiochemotherapy of advanced Rectal Cancer, there is only slight gender-related Differences, none in terms of Radiation Sensitivity! - Schuster, Barbara; Hecht, Markus; Schmidt, Manfred; Haderlein, Marlen; Jost, Tina; Geinitz, H.; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Investigation of a radioprotective Effect of the Kinase Inhibitor Palbociclib on Melanoma Cells in a 3D Cell Culture Model - Jost, Tina; Buerkel, F.; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36487

Kinase Inhibitor Palbociclib shows differential Effects upon Irradiation on Normal Tissue and Cancer Cell Lines - Jost, Tina; Proebstle, Stephanie; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36486

Kinase inhibitors increase individual radiation sensitivity in normal cells of cancer patients - Jost, Tina; Schuster, Barbara; Heinzerling, Lucie; Weissmann, Thomas; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Strahlentherapie und Onkologie, 2022)
Purpose Kinase inhibitors (KI) are known to increase radiosensitivity, which can lead to increased risk of side effects. Data about interactions of commonly used KI with ionizing radiation on healthy tissue are rare. Patients and methods Freshly drawn blood samples were analyzed using three-color FISH (fluorescence in situ hybridization) to measure individual radiosensitivity via chromosomal aberrations after irradiation (2 Gy). Thresholds of 0.5 and 0.6 breaks/metaphase (B/M) indicate moderate or clearly increased radiosensitivity. Results The cohorts consisted of healthy individuals (NEG, n = 219), radiosensitive patients (POS, n = 24), cancer patients (n = 452) and cancer patients during KI therapy (n = 49). In healthy individuals radiosensitivity (>= 0.6 B/M) was clearly increased in 5% of all cases, while in the radiosensitive cohort 79% were elevated. KI therapy increased the rate of sensitive patients (>= 0.6 B/M) to 35% significantly compared to 19% in cancer patients without KI (p = 0.014). Increased radiosensitivity of peripheral blood mononuclear cells (PBMCs) among patients occurred in six of seven KI subgroups. The mean B/M values significantly increased during KI therapy (0.47 +/- 0.20 B/M without compared to 0.50 +/- 0.19 B/M with KI, p = 0.047). Conclusions Kinase inhibitors can intensify individual radiosensitivity of PBMCs distinctly in 85% of tested drugs.
CRIS-Team WoS Importer:2022-05-13

Kinase Inhibitors increase the individual Radiation Sensitivity of Normal Tissue in Cancer Patients - Jost, Tina; Schuster, Barbara; Heinzerling, L.; Weissmann, Thomas; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Strahlentherapie und Onkologie, 2022)
CRIS-Team WoS Importer:2022-06-03

Kinase Inhibitors of DNA-PK, ATM and ATR in Combination with Ionizing Radiation Can Increase Tumor Cell Death in HNSCC Cells While Sparing Normal Tissue Cells - Faulhaber, Eva-Maria; Jost, Tina; Symank, Julia-Alice; Scheper, Julian; Burkel, Felix; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (Genes, 2021)
(1) Kinase inhibitors (KI) targeting components of the DNA damage repair pathway are a promising new type of drug. Combining them with ionizing radiation therapy (IR), which is commonly used for treatment of head and neck tumors, could improve tumor control, but could also increase negative side effects on surrounding normal tissue. (2) The effect of KI of the DDR (ATMi: AZD0156; ATRi: VE-822, dual DNA-PKi/mTORi: CC-115) in combination with IR on HPV-positive and HPV-negative HNSCC and healthy skin cells was analyzed. Cell death and cell cycle arrest were determined using flow cytometry. Additionally, clonogenic survival and migration were analyzed. (3) Studied HNSCC cell lines reacted differently to DDRi. An increase in cell death for all of the malignant cells could be observed when combining IR and KI. Healthy fibroblasts were not affected by simultaneous treatment. Migration was partially impaired. Influence on the cell cycle varied between the cell lines and inhibitors; (4) In conclusion, a combination of DDRi with IR could be feasible for patients with HNSCC. Side effects on healthy cells are expected to be limited to normal radiation-induced response. Formation of metastases could be decreased because cell migration is impaired partially. The treatment outcome for HPV-negative tumors tends to be improved by combined treatment.
CRIS-Team WoS Importer:2021-07-09

Kinase Inhibitors of DNA-PK, ATM and ATR in Combination with Ionizing Radiation Can Increase Tumor Cell Death in HNSCC Cells While Sparing Normal Tissue Cells - Jost, Tina; Faulhaber, Eva-Maria; Symank, Julia-Alice; Scheper, Julian; Bürkel, Felix; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Palbociclib Induces Senescence in Melanoma and Breast Cancer Cells and Leads to Additive Growth Arrest in Combination With Irradiation - Jost, Tina; Heinzerling, Lucie; Fietkau, Rainer; Hecht, Markus; Distel, Luitpold (Frontiers in Oncology, 2021)
Introduction: Several kinase inhibitors (KI) bear the potential to act as radiosensitizers. Little is known of the radiosensitizing effects of a wide range of other KI like palbociclib, which is approved in ER+/HER2- metastatic breast cancer. Method: In our study, we used healthy donor fibroblasts and breast cancer and skin cancer cells to investigate the influence of a concomitant KI + radiation therapy. Cell death and cell cycle distribution were studied by flow cytometry after Annexin-V/7-AAD and Hoechst staining. Cellular growth arrest was studied in colony-forming assays. Furthermore, we used C12-FDG staining (senescence) and mRNA expression analysis (qPCR) to clarify cellular mechanisms. Results: The CDK4/6 inhibitor palbociclib induced a cell cycle arrest in the G0/G1 phase. Cellular toxicity (cell death) was only slightly increased by palbociclib and not enhanced by additional radiotherapy. As the main outcome of the colony formation assays, we found that cellular growth arrest was induced by palbociclib and improved by radiotherapy in an additive manner. Noticeably, palbociclib treatment clearly induced senescence not only in breast cancer and partly in melanoma cells, but also in healthy fibroblasts. According to these findings, the downregulation of senescence-related FOXM1 might be an involved mechanism of the senescence-induction potential of palbociclib. Conclusion: The effect on cellular growth arrest of palbociclib and radiotherapy is additive. Palbociclib induces permanent G0/G1 cell cycle arrest by inducing senescence in fibroblasts, breast cancer, and melanoma cells. Direct cell death induction is only a minor secondary mechanism of action. Concomitant KI and radiotherapy is a strategy worth studying in clinical trials.
CRIS-Team Scopus Importer:2021-11-12
Keywords: breast cancer; kinase inhibitor; melanoma; palbociclib; radiotherapy; senescence

PARP inhibitors combined with ionizing radiation induce different effects in melanoma cells and healthy fibroblasts - Weigert, Verena; Jost, Tina; Hecht, Markus; Knippertz, Ilka; Heinzerling, Lucie; Fietkau, Rainer; Distel, Luitpold (BMC Cancer, 2020)
BACKGROUND: PARP inhibitors niraparib and talazoparib are FDA approved for special cases of breast cancer. PARP is an interesting repair protein which is frequently affected in cancer cells. We studied the combined action of talazoparib or niraparib with ionizing radiation in melanoma cells and healthy fibroblasts. METHODS: Homologous recombination (HR) status in six different melanoma cell lines and healthy fibroblasts was assessed. Cell cultures were treated with PARP inhibitors talazoparib or niraparib and ionizing radiation (IR). Apoptosis, necrosis and cell cycle distribution was analyzed via flow cytometry. Cell migration was studied by scratch assays. RESULTS: Studied melanoma cell cultures are HR deficient. Studied healthy fibroblasts are HR proficient. Talazoparib and niraparib have congruent effects within the same cell cultures. In all cell cultures, combined treatment increases cell death and G2/M arrest compared to IR. Combined treatment in melanoma cells distinctly increases G2/M arrest. Healthy fibroblasts are less affected by G2/M arrest. Treatment predominantly decelerates or does not modify migration. In two cell cultures migration is enhanced under the inhibitors. CONCLUSIONS: Although the two PARP inhibitors talazoparib and niraparib appear to be suitable for a combination treatment with ionizing radiation in our in vitro studies, a combination treatment cannot generally be recommended. There are clear interindividual differences in the effect of the inhibitors on different melanoma cells. Therefore, the effect on the cancer cells should be studied prior to a combination therapy. Since melanoma cells increase more strongly than fibroblasts in G2/M arrest, the fractional application of combined treatment should be further investigated.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Cell cycle; Cell death; Homologous recombination; Ionizing radiation; Kinase inhibitor; PARP1/PARP2; Radiosensitivity

PARP Inhibitors Talazoparib and Niraparib Sensitize Melanoma Cells to Ionizing Radiation - Jonuscheit, Stephanie; Jost, Tina; Gajdošová, Fritzi; Wrobel, Maximilian; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Genes, 2021)
(1) Background: Niraparib and Talazoparib are poly (ADP-ribose) polymerase (PARP) 1/2 inhibitors. It is assumed that combining PARP inhibitors with radiotherapy could be beneficial for cancer treatment. In this study, melanoma cells were treated with Niraparib and Talazoparib in combination with ionizing radiation (IR). (2) Methods: The effects of Talazoparib and Niraparib in combination with IR on cell death, clonogenicity and cell cycle arrest were studied in healthy primary fibroblasts and primary melanoma cells. (3) Results: The melanoma cells had a higher PARP1 and PARP2 content than the healthy fibroblasts, and further increased their PARP2 content after the combination therapy. PARP inhibitors both sensitized fibroblasts and melanoma cells to IR. A clear supra-additive effect of KI+IR treatment was detected in two melanoma cell lines analyzing the surviving fraction. The cell death rate increased in the healthy fibroblasts, but to a larger extent in melanoma cells after combined treatment. Finally, a lower percentage of cells in the radiosensitive G2/M phase is present in the healthy fibroblasts compared to the melanoma cells. (4) Conclusions: Both PARP inhibitors sensitize melanoma cells to IR. Healthy tissue seems to be less affected than melanoma cells. However, the great heterogeneity of the results suggests prior testing of the tumor cells in order to personalize the treatment.
CRIS-Team Scopus Importer:2021-06-18
Keywords: ionizing radiation; kinase inhibitors; PARP

Radiosensitizing and radioprotecting effect of kinase-inhibitor Palbociclib in different normal tissue and cancer cell lines - Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36494

Radiotherapy combined with docetaxel alters the immune phenotype of HNSCC cells and results in increased surface expression of CD137 and release of HMGB1 of specifically HPV-positive tumor cells - Grottker, Fridolin; Gehre, Simon; Reichardt, Clara; Sengedorj, Azzaya; Jost, Tina; Rieckmann, Thorsten; Hecht, Markus; Gostian, Antoniu-Oreste; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Rückert, Michael (Neoplasia, 2023)
Purpose: Human papilloma virus (HPV) positive head and neck squamous cell carcinoma (HNSCC) tumors respond significantly better to anticancer treatments. It is assumed to be due to a better response to radiotherapy (RT), and presumably to an increased immunogenicity. However, little is known how the immune phenotype of HNSCC tumor cells is modulated by standard treatment, namely by radiochemotherapy (RCT). Methods: Therefore, we aimed to examine the impact of the HPV status on the immune phenotype of HNSCC cell lines following RCT with 5 × 3Gy or 1 × 19.3Gy and/or docetaxel, by analyzing cell death, release of damage-associated molecular patterns (DAMPs), surface expression of immune checkpoint molecules (ICMs) and the impact on activation of human monocyte-derived dendritic cells (hmDCs). Results: Cell death induction and Hsp70 release following RCT was independent of the HPV status, and RCT significantly increased the expression of the immune suppressive ICMs PD-L1, PD-L2 and HVEM. An immune stimulatory ICM, CD137, was significantly increased following RCT only on HPV-positive cell lines, as well as the release of HMGB1. Although the treatment increased cell death and modulated ICM expression in HNSCC, the hmDCs were not activated after co-incubation with treated tumor cells. Conclusion: Our data with the HPV-dependent release of HMGB1 and increased expression of CD137 following RCT provide a hint for increased immunogenicity underlining the better prognosis for HPV positive tumors following RCT.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Anti-tumor immunity; Dendritic cells; Docetaxel; Head and neck squamous cell carcinoma; HMGB1; HPV status; Immune checkpoint molecules; Radiotherapy

Senescence Induction by Combined Ionizing Radiation and DNA Damage Response Inhibitors in Head and Neck Squamous Cell Carcinoma Cells - Dobler, Clara; Jost, Tina; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Cells, 2020)
DNA damage response inhibitors (DDRi) may selectively enhance the inactivation of tumor cells in combination with ionizing radiation (IR). The induction of senescence may be the key mechanism of tumor cell inactivation in this combinatorial treatment. In the current study the effect of combined IR with DDRi on the induction of senescence was studied in head and neck squamous cell carcinoma (HNSCC) cells with different human papilloma virus (HPV) status. The integrity of homologous recombination (HR) was assessed in two HPV positive, two HPV negative HNSCC, and two healthy fibroblast cell cultures. Cells were treated with the DDRi CC-115 (DNA-dependent protein kinase, DNA-pK; dual mammalian target of rapamycin, mTor), VE-822 (ATR; ataxia telangiectasia and Rad3-related kinase), and AZD0156 (ATM; ataxia telangiectasia mutated kinase) combined with IR. Effects on senescence, apoptosis, necrosis, and cell cycle were analyzed by flow cytometry. The fibroblast cell lines generally tolerated IR or combined treatment better than the tumor cell lines. The ATM and ATR inhibitors were effectively inducing senescence when combined with IR. The DNA-PK inhibitor was not an important inductor of senescence. HPV status and HR activity had a limited influence on the efficacy of DDRi. Induction of senescence and necrosis varied individually among the cell lines due to molecular heterogeneity and the involvement of DNA damage response pathways in senescence induction.
CRIS-Team Scopus Importer:2020-10-30
Keywords: ATM; ATR; DNA damage response inhibitor; DNAPK; HNSCC; homologous recombination; ionizing radiation; kinase inhibitor; radiosensitivity; senescence

The Effect of Ionizing Irradiation on the Autotaxin-Lysophasphatidic Acid Axis and Interleukin-6/8 Secretion in Different Breast Cancer Cell Lines - Promny, Theresa; Scherrer, Isabell; Kadam, Sheetal; Schmid, Rafael; Jost, Tina; Distel, Luitpold; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2024)
Background: The Autotaxin (ATX)-lysophosphatidic acid (LPA) axis is involved in decreasing radiation sensitivity of breast tumor cells. This study aims to further elucidate the effect of irradiation on the ATX-LPA axis and cytokine secretion in different breast cancer cell lines to identify suitable breast cancer subtypes for targeted therapies. Methods: Different breast cancer cell lines (MCF-7 (luminal A), BT-474 (luminal B), SKBR-3 (HER2-positive), MDA-MB-231 and MDA-MB-468 (triple-negative)) and the breast epithelial cell line MCF-10A were irradiated. The influence of irradiation on LPA receptor (LPAR) expression, ATX expression, and Interleukin (IL)-6 and IL-8 secretion was analyzed. Further, the effect of IL-6 and IL-8 on ATX expression of adipose-derived stem cells (ADSC) was investigated. Results: Irradiation increased ATX and LPAR2 expression in MDA-MB-231 cells. Additionally, IL-6 secretion was enhanced in MDA-MB-231, and IL-8 secretion in MDA-MB-231 and MDA-MB-468. Stimulation of ADSC with IL-6 and IL-8 increased ATX expression in ADSC. Conclusions: Targeting ATX or its downstream signaling pathways might enhance the sensitivity of triple-negative breast cancer cells to radiation. Further exploration of the interplay between irradiation, the ATX-LPA axis, and inflammatory cytokines may elucidate novel pathways for overcoming radioresistance and improving individual treatment outcomes.
CRIS-Team Scopus Importer:2024-10-11
Keywords: adipose-derived stem cells; ADSC; ATX; inflammatory mediators; LPA receptors; lysophosphatidate signaling

The Impact of Irradiation and Lipotransfer on Healthy Mammary Cells after Breast-Conserving Surgery - Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kengelbach-Weigand, Annika; Hauck, Theresa; Horch, Raymund E. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Tumor-specific radiosensitizing effect of the ATM inhibitor AZD0156 in melanoma cells with low toxicity to healthy fibroblasts - Scheper, Julian; Hildebrand, Laura; Faulhaber, Eva-Maria; Deloch, Lisa; Gaipl, Udo; Symank, Julia-Alice; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus; Jost, Tina (Strahlentherapie und Onkologie, 2022)
Purpose Despite new treatment options, melanoma continues to have an unfavorable prognosis. DNA damage response (DDR) inhibitors are a promising drug class, especially in combination with chemotherapy (CT) or radiotherapy (RT). Manipulating DNA damage repair during RT is an opportunity to exploit the genomic instability of cancer cells and may lead to radiosensitizing effects in tumors that could improve cancer therapy. Methods A panel of melanoma-derived cell lines of different origin were used to investigate toxicity-related clonogenic survival, cell death, and cell cycle distribution after treatment with a kinase inhibitor (KI) against ATM (AZD0156) or ATR (VE-822, berzosertib), irradiation with 2 Gy, or a combination of KI plus ionizing radiation (IR). Two fibroblast cell lines generated from healthy skin tissue were used as controls. Results Clonogenic survival indicated a clear radiosensitizing effect of the ATM inhibitor (ATMi) AZD0156 in all melanoma cells in a synergistic manner, but not in healthy tissue fibroblasts. In contrast, the ATR inhibitor (ATRi) VE-822 led to additive enhancement of IR-related toxicity in most of the melanoma cells. Both inhibitors mainly increased cell death induction in combination with IR. In healthy fibroblasts, VE-822 plus IR led to higher cell death rates compared to AZD0156. A significant G2/M block was particularly induced in cancer cells when combining AZD0156 with IR. Conclusion ATMi, in contrast to ATRi, resulted in synergistic radiosensitization regarding colony formation in melanoma cancer cells, while healthy tissue fibroblasts were merely affected with respect to cell death induction. In connection with an increased number of melanoma cells in the G2/M phase after ATMi plus IR treatment, ATMi seems to be superior to ATRi in melanoma cancer cell treatments when combined with RT.
CRIS-Team WoS Importer:2022-10-28

Tumor-specific Toxicity to malignant Melanoma Cells by the dual DNA-PK and mTOR Inhibitor CC115 in Combination with ionizing Radiation - Burkel, F.; Jost, Tina; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36482

Wirkung von Flap Endonuclease 1 Inhibitor FEN1-IN-4 in Kombination mit ionisierender Strahlung auf Mammakarzinomzellen - Berfelde, Johanna; Hildebrand, Laura; Jost, Tina; Distel, Luitpold; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)